A Six‐Crossing Doubly Interlocked [2]Catenane with Twisted Rings, and a Molecular Granny Knot. Issue 42 (19th September 2018) - Danon, Jonathan J.; Leigh, David A.; Pisano, Simone; Valero, Alberto; Vitorica‐Yrezabal, Iñigo J.
Abstract: A molecular 6 2 3 link (a six crossing, doubly interlocked, [2]catenane with twisted rings) and a 31 #31 granny knot (a composite knot made up of two trefoil tangles of the same handedness) were constructed by ring‐closing olefin metathesis of an iron(II)‐coordinated 2×2 interwoven grid. The connections were directed by pendant phenyl groups to be between proximal ligand ends on the same faces of the grid. The 6 2 3 link was separated from the topoisomeric granny knot by recycling size‐exclusion chromatography. The identity of each topoisomer was determined by tandem mass spectrometry and the structure of the 6 2 3 link confirmed by X‐ray crystallography, which revealed two 82‐membered macrocycles, each in figure‐of‐eight conformations, linked through both pairs of loops. Abstract : Linked in : The synthesis of a molecular 6 2 3 link and a 31 #31 granny knot from a 2×2 interwoven grid is described. The two topoisomers were separated by exhaustive recycling size‐exclusion chromatography and their identities determined by tandem mass spectrometry. The X‐ray crystal structure of the metal‐free 6 2 3 link was obtained.